From "Guest" to Occupier? Unstable Hospitality and the Ahistoricity of Tropology in the Discourse of Rhetoric. - Sharon-Zisser, Shirley (Philosophy & Rhetoric, 1999)
The article reports that treatises on the art of rhetoric anasemically bespeak an underlying conception of language as a perilous and far-from-neutral medium. Although this underlying conception is largely unconscious and hidden, it occasionally erupts to the surface of explicit articulation in telling, symptomatic ways. Since they unconsciously associate language with the archaic, engulfing, maternal body, with the "limitless extension" and unpredictable diffusion of the oceanic state of predivision, with the "intra-uterine" unicity that is the site of a primal narcissism, the authors of such treatises unconsciously yet consistently struggle to reproduce it as a differentiated, partitioned symbolic economy' that is gravitating to a phallicized general equivalent. The reinvention of a linguistic substance that is unconsciously imagined as the engulfing, maternal body or a highly differentiated phallocentric symbolic economy of rhetoric, where "partial" rather than "cohesive" pulsions "reign and master" is carried out by means of a discursive mechanism that involves ideologically inflected definitions and hierarchizing partitions of the forms of language articulated by means of an unstable crossing of the registers of discourse, including those of love and desire, money and property, gynecology and gender, hospitality and conquest.